Closed pulmonary valvotomy in infants under 6 months of age: report of 14 consecutive cases without mortality. Issue 11 (November 1980) - Milo, S; Yellin, A; Smolinsky, A; Blieden, L C; Neufeld, H N; Goor, D A
Abstract : Fourteen infants, all under 6 months of age, underwent surgery for the relief of severe valvar pulmonary stenosis. A modified Brock (transinfundibular valvotomy) procedure was performed in all cases. Dilatation of the pulmonary valve with a mosquito clamp and biliary dilator is the basis of the modified operation. All infants survived the operation. In two patients there is residual, significant pulmonary stenosis, and in two additional cases pulmonary regurgitation is present.